Liver failure following biliopancreatic diversions: a narrative review - Cazzo, Everton; Pareja, José Carlos; Chaim, Elinton Adami (São Paulo Medical Journal, 2017)
CONTEXT AND OBJECTIVE: Occurrences of liver failure following jejunoileal bypass were extensively reported in the past and were one of the main factors that led to abandonment of this procedure. The newer predominantly malabsorptive procedures called biliopancreatic diversions (BPDs) have also been implicated in several cases of acute and subacute liver failure. The aim here was to review the current available evidence on occurrences of liver failure following BPDs. DESIGN AND SETTING: Narrative review; bariatric surgery service of a public university hospital. METHODS: A review of the literature was conducted through an online search of medical databases. RESULTS: Associations between BPDs and liver failure have only infrequently been reported in the literature. However, they appear to be more than merely anecdotal. The pathophysiological mechanisms remain obscure, but they seem to be related to rapid weight loss, protein malnutrition, deficits of hepatotrophic factors, high circulating levels of free fatty acids and bacterial overgrowth in the bypassed bowel segments. Reversal of the BPD may ameliorate the liver impairment. CONCLUSIONS: Although infrequent, liver failure remains a concern following BPDs. Careful follow-up is required in individuals who undergo any BPD.